2016
DOI: 10.1111/pan.12930
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative management of living‐donor liver transplantation for methylmalonic acidemia

Abstract: Methymalonic acidemia (MMA) is a hereditary metabolic disorder characterized by a defect of the methylmalonyl-CoA mutase that breaks down propionate. The efficacy of liver transplantation for MMA was recently reported. However, the anesthetic management of liver transplant for MMA is not clear. The aim of this article is to describe an anesthetic management algorithm of liver transplant for MMA by reviewing our cases of liver transplant for MMA. Fourteen patients received a liver transplant; three cases showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…Since hypoglycemia worsens metabolic acidosis by protein catabolism sthenia, glucose loading should be avoided. Preoperative fasting should be as short as possible; some studies have reported 6 h as an optimal fasting time [2]. If necessary, glucose may be administered during preoperative fasting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since hypoglycemia worsens metabolic acidosis by protein catabolism sthenia, glucose loading should be avoided. Preoperative fasting should be as short as possible; some studies have reported 6 h as an optimal fasting time [2]. If necessary, glucose may be administered during preoperative fasting.…”
Section: Discussionmentioning
confidence: 99%
“…In general, propofol should also not be administered to patients with MMA. One study reported that propofol use was associated with deterioration of metabolic failure during general anesthesia in a living liver transplantation [2]. Another study has suggested that propofol may be safe for continuous intravenous administration, which was used for sedation during procedures such as magnetic resonance imaging [5].…”
Section: Discussionmentioning
confidence: 99%
“…The guidelines for diagnosis and management of MMAemia suggest that LT should be considered in patients with MMAemia who suffer frequent metabolic acidosis despite dietary and medical treatment [1]. A report on 14 cases of LT for MMAemia in a single institute in Japan showed that severe metabolic acidosis occurred in 3 cases at the start of the operation, and death occurred perioperatively in 2 of these 3 cases [4]. Thus, metabolic acidosis should be prevented during LT, even though the prognosis of MMAemia after LT has recently been improved [4].…”
Section: Discussionmentioning
confidence: 99%
“…A report on 14 cases of LT for MMAemia in a single institute in Japan showed that severe metabolic acidosis occurred in 3 cases at the start of the operation, and death occurred perioperatively in 2 of these 3 cases [4]. Thus, metabolic acidosis should be prevented during LT, even though the prognosis of MMAemia after LT has recently been improved [4]. In a patient with MMAemia, MMA accumulation can cause metabolic acidosis and secondary mitochondrial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation